The Far Right in Sweden: from Neo-nazism to Centrism - A. S. Badaeva (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
The author explores the farright wing of the political spectrum in Sweden. A small retrospective to the works of Per Engdahl allows us to identify certain similarities between modern Swedish farright organizations and their ethnonationalist postwar precursors. The author divides the farright wing into two parts: radicals (mainly neoNazis and extremists) and moderates, which offer a special refined strategy of nationalism. Special attention is paid to Sweden Democrats (SD). For 30 years, this party transformed from a small neoNazi marginal organization into the third largest national conservative political force in Sweden, according to the results of the 2018 parliamentary election and of the 2019 European election. The farright Sweden Democrats entry in Riksdag promoted the qualitative and quantitative change of the party political system in Sweden. It’s fragmentarily increased. The former balance of power has shifted. The two largest Swedish Social Democratic and Moderate Parties, traditionally forming centreleft and centreright blocks, have substantially lost their public sympathy. Trying to keep power, the governance parties are involving in common political trend: they are actively using narrative of rightwing populism and are ready to previously unthinkable party alliances erasing usual ideological boundaries. The total political isolation makes Sweden Democrats move their attitudes towards the center too. Meanwhile there are several new radical right  parties (Nordic Resistance Movement (NRM), Alternative for Sweden (AfS), which are setting Sweden Democrats off as a social conservative force.